Surface free energy of the human skin and its critical surface tension of wetting in the skin/surfactant aqueous solution/air system. Issue 2 (14th August 2014) - Krawczyk, J.
<x xml:space="preserve">Abstract</x> Background/purpose The purpose of these studies was to determine the surface free energy of the human skin and its critical surface tension of wetting in the skin – surfactant aqueous solution – air system in relation to different types of surfactants. Methods The surface free energy of the skin and its components was calculated using the equilibrium advancing contact angle values of water, formamide, and diiodomethane on the forearm skin surface. Next, taking into account the measured values of the contact angle of aqueous solutions of SDDS, CTAB, TX‐100 and TX‐114 on the skin surface and data of their surface tension, the critical surface tension of the skin wetting was determined. Results We can classify the skin surface as low‐energetic one. The critical surface tension of the skin wetting depends on the type of surfactant. Conclusion It is possible to determine the critical surface tension of the human skin wetting on the basis of the values of the contact angle of aqueous solutions of surfactants and their surface tension. In this respect, nonionic surfactants seem to be the most appropriate.